Famous in a small town - Mills, Emma, 1989- (New York : Henry Holt and Company, 2019)
Tasked with getting her school's marching band to the Rose Parade, Sophie tries to persuade her small town's only claim to fame, country singer Megan Pleasant, to return to town and help her raise the funds.
Keywords: High school students -- Fiction; Women singers -- Fiction; Friendship -- Fiction; Love -- Fiction; Marching bands -- Fiction; Fund raising -- Fiction; Small cities -- Fiction; High school students -- Fiction; Women singers -- Fiction; Friendship -- Fiction; Marching bands -- Fiction; Fund raising -- Fiction; Cities and towns -- Fiction; Romance fiction